Handbook of research on overcoming digital divides constructing an equitable and competitive information society - Ferro, Enrico; Dwivedi, Yogesh Kumar; Gil García, José Ramón; Williams, Michael D. (Information Science Reference, 2010)
"This book presents a comprehensive, integrative, and global view of what has been called the digital divide" - Provided by publisher
Includes bibliographical references and index
Druckausgabe in 2 Bänden erschienen
Keywords: Informationsgesellschaft; Überwindung; Digitale Spaltung; Aufsatzsammlung